2018
DOI: 10.1080/0144929x.2018.1485745
|View full text |Cite
|
Sign up to set email alerts
|

Towards EEG-based BCI driven by emotions for addressing BCI-Illiteracy: a meta-analytic review

Abstract: Many critical aspects affect the correct operation of a Brain Computer Interface. The term "BCIilliteracy" describes the impossibility of using a BCI paradigm. At present, a universal solution does not exist and seeking innovative protocols to drive a BCI is mandatory. This work presents a meta-analytic review on recent advances in emotions recognition with the perspective of using emotions as voluntary, stimulus-independent, commands for BCIs. 60 papers, based on electroencephalography measurements, were sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 125 publications
0
10
0
2
Order By: Relevance
“…Consumer-grade devices, although not accurate enough for neuroscience research and critical control tasks, have been reported to be a feasible choice for applications such as affective computing (Duvinage et al, 2013;Nijboer et al, 2015;Maskeliunas et al, 2016). ER by EEG has been widely explored in the literature (Alarcao and Fonseca, 2017;Spezialetti et al, 2018). Most commonly used features can be roughly classified by the domain from which they are extracted (time, frequency, time-frequency).…”
Section: Brain Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Consumer-grade devices, although not accurate enough for neuroscience research and critical control tasks, have been reported to be a feasible choice for applications such as affective computing (Duvinage et al, 2013;Nijboer et al, 2015;Maskeliunas et al, 2016). ER by EEG has been widely explored in the literature (Alarcao and Fonseca, 2017;Spezialetti et al, 2018). Most commonly used features can be roughly classified by the domain from which they are extracted (time, frequency, time-frequency).…”
Section: Brain Activitymentioning
confidence: 99%
“…ER by EEG has been widely explored in the literature (Alarcao and Fonseca, 2017 ; Spezialetti et al, 2018 ). Most commonly used features can be roughly classified by the domain from which they are extracted (time, frequency, time–frequency).…”
Section: State Of the Artmentioning
confidence: 99%
“…Affective computing researches aim to furnish computers with emotional intelligence [51] to allow them to be genuinely intelligent and support natural human-machine interaction (HMI). Emotion recognition has several applications in different areas such as marketing [18], safe and autonomous driving [22], mental health monitoring [17], brain-computer interfaces [65], social security [75], robotics [55].…”
Section: Introductionmentioning
confidence: 99%
“…Una Interfaz Cerebro computador (BCI) usa señales del cerebro que proporcionan un método directo de comunicación entre una computadora y otros dispositivos, una BCI puede ayudar a reestablecer la comunicación con personas que sufrieron un trastorno de movimiento (Thompsona, 2017). Una BCI proporciona herramientas de control hacia un entorno externo como una alternativa a las vías tradicionales como son músculos y nervios y son basados en la monitorización directa de la actividad cerebral (M. Spezialetti, 2018).…”
Section: Introductionunclassified